RELIGIOUS FREEDOM IN TIMES OF WAR (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2018)
War is a conflict spanning over a certain period of time in order to defend various interests. Religious freedom, on the other hand, is the fundamental right that guarantees one’s freedom to act according to their own conscience, the interior forum of ideas and concepts, even in times of war. A central figure of natural law theories, Hugo Grotius claims that God, the Creator, endowed each individual with will and reason, and therefore these rights should be defended and respected. An example of what happens when this right to freedom of religion and belief is defended regardless of the situation is the American conscientious objector hero Desmond Doss, awarded with the Congressional Medal of Honor for acts of valor.